Evaluation of Reference Genes for Quantitative PCR in Four Tissues from Rabbits with Hypercholesterolaemia - Zhang,Zhen (2019)
Abstract Rabbit with hypercholesterolaemia is an important model for studying cholesterol metabolism disease. This study aimed to evaluate the expression stability of nine reference genes for quantitative PCR (qPCR) analysis in adrenal gland, liver, spleen, and kidney tissue from rabbits with hypercholesterolaemia. In total, 30 male Harbin Large White (HLW) rabbits were fed a normal feed (n = 15) or a high cholesterol feed (n = 15) for 8 weeks to induce hypercholesterolaemia. Nine reference genes were verified by qPCR using cDNA extracted from rabbit tissue samples. For qPCR analysis, reference genes were evaluated using the RefFinder and GeNorm algorithms. Overall, seven rabbits with hypercholesterolaemia were identified based on body weight and total cholesterol measurements. Combining the results of the RefFinder and GeNorm algorithms, the most stable reference genes were hypoxanthine phosphoribosyltransferase 1 (Hprt1) and eukaryotic translation elongation factor 1 alpha 1 (Eef1a1) in the adrenal gland, β-2-microglobulin (B2m) and glyceraldehyde-3-phosphate dehydrogenase (Gapdh) in the liver, tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (Ywhaz) and Gapdh in the spleen, and peptidylprolyl isomerase (Ppia), β-actin (Actb), succinate dehydrogenase complex subunit A ﬂavoprotein (Sdha), and B2m in the kidney. Taken together, our results confirmed that Hprt1 and Eef1a1, B2m and Gapdh, Ywhaz and Gapdh, and Ppia, Actb, Sdha, and B2m were the best reference genes for qPCR analyses in adrenal gland, liver, spleen, and kidney tissue, respectively, of rabbits with hypercholesterolaemia.